An evaluation of the Fisher Hem-Alyzer - Lappin, T. R. J. (1970)
The Fisher Hem-Alyzer is a multitest sequential discrete analyser with automatic printout of digitized results on paper tape. The instrument is well designed, soundly constructed, and reliable in routine use. Cross contamination from the sampler probe or between the cuvettes is minimal. Accuracy and precision are both highly satisfactory. Although the standard rate of throughput is 32 specimens per hour the instrument can be used at irregular intervals to analyse smaller batches or even individual specimens. In a routine daily service the Hem-Alyzer was capable of handling a workload of 200 specimens per day, requiring three hours of laboratory technician time. The Hem-Alyzer produces only three parameters. By not determining the packed cell volume it is not possible to incorporate the derived indices (MCV and MCHC) into the system and this, in the long term, is bound to be a disadvantage.